Fuzzy Control Analysis with Back-EMF in Washing Machines - Min-yan DI (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper puts forward a method of detecting material and quantity of the cloth in washing machine based on detection motor back EMF, not only can obtain the pulse number of reporting the information quality and quantity of the cloth, but also can collect information of pulse width, the pulse cycle , help to improve the detection accuracy of the material and quantity of the cloth. On this basis, This article also gives a specific control rules of the fuzzy control of automatic washing machine , With this fuzzy control rule table, off-line Fuzzy control response can be obtained. Finally enquiry form  used to Program of assembly language, determined material and quantity and dirty degree of the cloth, to achieve the best effect of clothes washing by selecting water level, flow intensity, put the amount of detergent and washing time DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5098